The MusIC method: a fast and quasi-optimal solution to the muscle forces estimation problem. Issue 2 (25th January 2018) - Muller, A.; Pontonnier, C.; Dumont, G.
Abstract: The present paper aims at presenting a fast and quasi-optimal method of muscle forces estimation: the MusIC method. It consists in interpolating a first estimation in a database generated offline thanks to a classical optimization problem, and then correcting it to respect the motion dynamics. Three different cost functions – two polynomial criteria and a min/max criterion – were tested on a planar musculoskeletal model. The MusIC method provides a computation frequency approximately 10 times higher compared to a classical optimization problem with a relative mean error of 4% on cost function evaluation.